Demonstrating the applicability of chemical looping combustion for fluid catalytic cracking unit as a novel CO2 capture technology - Güleç, Fatih (2020)
Fluid Catalytic Cracking (FCC) units are responsible for ~25% of CO2 emissions released from the oil refineries, which themselves account for 4-6% of total global CO2 emissions. Although post- and oxy-combustion technologies have been suggested to capture the CO2 released from the regenerator of FCC, Chemical Looping Combustion (CLC) may also be a potential approach to capture the CO2 released from the regenerators in FCC units with lower energy consumption.